MATEC Web of Conferences - Naumkin, A. S. (EDP Sciences, 2018)
Mathematical model of burning disposal a water-methanol solution by the gas fuel is presented. Two-dimensional model in the ANSYS Fluent Software is made. Thermal distribution of the flare and distribution of methane concentration are derived. We analysed the results of mathematical modelling.